2008
DOI: 10.1007/s10447-008-9060-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Supervisory Experience, Counseling Experience, and Training in Supervision to Supervisory Identity Development

Abstract: The relationship between supervisory identity development and supervisory experience, counseling experience, and training in supervision was examined for Association for Counselor Education and Supervision (ACES) members. Analyses indicated that supervisory experience and training were related to supervisory identity development, whilst counseling experience was not. The implications of these findings are discussed in relation to the importance of supervisor credentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
0
17
1
2
Order By: Relevance
“…One study (Pelling, 2008) reported data on experience, but it was not usable in the VG because it did not contain the information required to calculate an effect size. Table 3 presents the details of the studies included in the VG analyses.…”
Section: Validity Generalization: Experiencementioning
confidence: 95%
See 4 more Smart Citations
“…One study (Pelling, 2008) reported data on experience, but it was not usable in the VG because it did not contain the information required to calculate an effect size. Table 3 presents the details of the studies included in the VG analyses.…”
Section: Validity Generalization: Experiencementioning
confidence: 95%
“…This statistic indicates whether there is sufficient evidence to reject the null hypothesis that (Hillman et al, 1998) Peer-reviewed journal 43 103.9 11.2 (Bencivenne, 1999) Unpublished dissertation 136 110.0 8.9 (Baker et al, 2002) Peer-reviewed journal 19 84.2 14.2 (Barnes, 2002) Unpublished dissertation 255 107.0 11.9 (Vidlak, 2002) Unpublished dissertation 99 103.3 8.0 (Culbreth & Cooper, 2008) Peer-reviewed journal 192 -- (Lyon et al, 2008) Peer-reviewed journal 233 90.6 12.5 (Pelling, 2008) Peer all of the studies share a common effect size. The I 2 statistic was also calculated, which indicates the extent to which the observed heterogeneity in reliability estimates is due to true variability across samples.…”
Section: Reliability Generalizationmentioning
confidence: 98%
See 3 more Smart Citations